Drug-like properties of potential anti-cancer compounds from Cameroonian flora: A virtual studies - Ibezim Akachukwu, Onyia Kelechi, Ntie-Kang Fidele, Nwodo Ngozi Justina (Journal of Applied Pharmaceutical Science, 2015)
Assessment of the ‘drug-like’ using a set of calculated molecular descriptors, of a collection of 195compounds from plants in Cameroon exhibiting in vitro or/and in vivo activities against various cancer cell lines was made. Lipinski’s ‘Rule of Five’ (Ro5) was used to evaluate drug-likeness/oral availability of the compounds by making use of popular parameters like Molecular Weight (MW), predicted lipophilicity (log P), number of Hydrogen Bond Donors/Acceptors (HBD and HBA) and Number of Rotatable Bonds (NRB). The drug-like properties of the studied compounds were compared to that of the Dictionary of Natural Products (DNP). Our results revealed that79.50%, 43.60% and 12.30% of our dataset fall within the recommended range for ‘drug-like’, ‘lead-like’ and ‘fragment-like’ respectively with significant enhancement of some oral availability parameters over DNP and this paints the significant of our dataset in search for lead-like anti-cancer molecules with desirable ‘drug-like’ properties.
Keywords: Cancer, Natural products, Drug-likeness, Physico-chemical properties.